Airway abundance of Haemophilus influenzae predicts response to azithromycin in adults with persistent uncontrolled asthma. Issue 4 (1st October 2020) - Taylor, Steven L.; Ivey, Kerry L.; Gibson, Peter G.; Simpson, Jodie L.; Rogers, Geraint B.
Long-term azithromycin treatment reduced exacerbations in adults with persistent symptomatic asthma in the AMAZES trial (Australian and New Zealand Clinical Trials Registry (ANZCTR), number 12609000197235) [1]. However, response to treatment was variable between participants and the characteristics of those who experience most clinical benefit have not been determined. The inability to define a specific population who are more responsive limits the ability to personalise this therapy, which is the goal for airways disease management [2]. With recent studies identifying airway Haemophilus influenzae colonisation as a candidate marker for asthma subgrouping [3, 4], we assessed whether H. influenzae abundance, measured using quantitative PCR (qPCR) [5, 6], predicted the ability of azithromycin therapy to reduce the incidence of acute asthma exacerbations. Sputum Haemophilus influenzae load predicts response to azithromycin in adults with persistent uncontrolled asthma: secondary findings from the AMAZES trial https://bit.ly/3f3tJ71